The basic reproduction number (R0) of ebola virus disease: A systematic review and meta-analysis - Basilua Andre Muzembo; Kei Kitahara; Debmalya Mitra; Ngangu Patrick Ntontolo; Nlandu Roger Ngatu; Ayumu Ohno; Januka Khatiwada; Shanta Dutta; Shin-Ichi Miyoshi (Travel Medicine and Infectious Disease, 2024)
Background: Ebola virus disease (Ebola) is highly pathogenic, transmissible, and often deadly, with debilitating consequences. Superspreading within a cluster is also possible. In this study, we aim to document Ebola basic reproduction number (R0): the average number of new cases associated with an Ebola case in a completely susceptible population. Methods: We undertook a systematic review and meta-analysis. We searched PubMed, EMBASE, and Web of Science for studies published between 1976 and February 27, 2023. We also manually searched the reference lists of the reviewed studies to identify additional studies. We included studies that reported R0 during Ebola outbreaks in Africa. We excluded studies that reported only the effective reproduction number (Rt). Abstracting data from included studies was performed using a pilot-tested standard form. Two investigators reviewed the studies, extracted the data, and assessed quality. The pooled R0 was determined by a random-effects meta-analysis. R0 was stratified by country. We also estimated the theoretically required immunization coverage to reach herd-immunity using the formula of (1-1/R0) × 100 %. Results: The search yielded 2042 studies. We included 53 studies from six African countries in the systematic review providing 97 Ebola mean R0 estimates. 27 (with 46 data points) studies were included in the meta-analysis. The overall pooled mean Ebola R0 was 1.95 (95 % CI 1.74–2.15), with high heterogeneity (I2 = 99.99 %; τ2 = 0.38; and p < 0.001) and evidence of small-study effects (Egger's statistics: Z = 4.67; p < 0.001). Mean Ebola R0 values ranged from 1.2 to 10.0 in Nigeria, 1.1 to 7 in Guinea, 1.14 to 8.33 in Sierra Leone, 1.13 to 5 in Liberia, 1.2 to 5.2 in DR Congo, 1.34 to 2.7 in Uganda, and from 1.40 to 2.55 for all West African countries combined. Pooled mean Ebola R0 was 9.38 (95 % CI 4.16–14.59) in Nigeria, 3.31 (95 % CI 2.30–4.32) in DR Congo, 2.0 (95 % CI 1.25–2.76) in Uganda, 1.83 (95 % CI 1.61–2.05) in Liberia, 1.73 (95 % CI 1.47–2.0) in Sierra Leonne, and 1.44 (95 % CI 1.29–1.60) in Guinea. In theory, 50 % of the population needs to be vaccinated to achieve herd immunity, assuming that Ebola vaccine would be 100 % effective. Conclusions: Ebola R0 varies widely across countries. Ebola has a much wider R0 range than is often claimed (1.3–2.0). It is possible for an Ebola index case to infect more than two susceptible individuals.